Diversities in the Indian diaspora : nature, implications, responses - Jayaram, N. (Oxford India paperbacks, 2012)
Papers presented at a seminar jointly organized by Indian Institute of Advanced Study, Shimla and the Institute for Social and Economic Change, held at Bangalore during May 7-9, 2008.